Angklung Sered Balandongan: Pelestarian dan Pembudayaannya di Kabupaten Tasikmalaya Tahun 1995-2017 - Amelia, Tia (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This research describes the preservation and enculturation of Angklung Sered Balandongan in Tasikmlaya District in 1995-2017. This research comes from the confusion and anxiety of the arts Angklung researchers Sered balandongan which until now has not been widely recognized by the public. Even had extinguished before finally start there research by artists who later developed in the area of education. Broadly speaking, this study answers the question "How is the preservation and enculturation of Angklung Sered Balandongan in Tasikmalaya district in 1995-2017". To answer these questions, researchers conducted a study using the historical method consists of the collection of source, source criticism, interpretation and historiography. Based on the research found that balandongan Sered Angklung art is an art that has long existed in Tasikmalaya regency. Nevertheless, Angklung Sered balandongan not widely known by the public. Therefore the artists and the government together to preserve and cultivate the arts.